Escrever: navegações a um canto por vir - Valverde, Juliana de Almeida (2021)
This study is an impulse towards the movement of a writing that experiences itself navigating through the perception of a landscape to come of writing. The hypothesis is that its outflow potentiates encounters with the creative principle and its secrets, overflowing to further navigations when considering that a writing event (the act of subjecting oneself to the writing movement) promotes an experience tied to time, space, and subject metamorphoses. The aim of this study is: to approach from the secrets of writing to the mystery of the song of the sirens; to question how the presence of a writing can unfold itself via the perception in different landscapes of writing; to move towards a phenomenology of the creative writing; to inquire the links of recollection and sensation with the creation; and to pay attention to the writing that is on the way, taking the errancy and the recommencement into account, both incessant, putting the writing in the middle, without beginning or end. This work is justified by the expansion of the critical fortune on creative writing, contributing to the dissemination of the studies related to the (artistic) creation, from the creators’ perspective. We echo mainly ideas from the essay “The Song of the Sirens”, by Maurice Blanchot (2005), evoking the metamorphoses through the experience in Marcel Proust (1988); as well as the landscape poetics and the perceptive subject in Michel Collot (2013); the phenomenology of perception in Merleau-Ponty (2018); the rhizome and the body without organs in Deleuze and Guattari (2011; 2012); and Sensationism in Fernando Pessoa (1974). This study takes a chance on a more experimental format and is associated with scientific work in the literary field that aims to contribute to bringing science and art closer together